2017
DOI: 10.2741/4514
|View full text |Cite
|
Sign up to set email alerts
|

The NF-kB regulates the SHP-1 expression in monocytes in congestive heart failure

Abstract: It has been shown that functional recovery of patients with acute congestive heart failure (ACHF) after treatment with conventional drugs (CD) is mediated by suppression of inflammation in peripheral blood mononuclear cells. Here, we analyzed gene expression profiles of monocytes from symptomatic ACHF patients (NYHA Class III-IV) before and after pharmacological treatment with CD. The treatment was associated with selective down-regulation of "TNFR signaling" and pro-inflammatory mediators CCL5, MIP-1α recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Taking advantage of contemporary bioinformatics approaches, we previously showed that PTPN6 plays a vital role in cellular responses to Al 2 O 3 NPs exposure [ 14 ]. With respect to the up-stream regulator of PTPN6, activation of pro-inflammatory pathway as well as oxidative stress have been reported to suppress the expression of PTPN6 [ 41 , 42 ]. Suppression of PTPN6 recruits neutrophil to the injury site and increases neutrophil adhesion in vivo ; however, overwhelming accumulation of neutrophils in the tissue may also cause damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of contemporary bioinformatics approaches, we previously showed that PTPN6 plays a vital role in cellular responses to Al 2 O 3 NPs exposure [ 14 ]. With respect to the up-stream regulator of PTPN6, activation of pro-inflammatory pathway as well as oxidative stress have been reported to suppress the expression of PTPN6 [ 41 , 42 ]. Suppression of PTPN6 recruits neutrophil to the injury site and increases neutrophil adhesion in vivo ; however, overwhelming accumulation of neutrophils in the tissue may also cause damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%